Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.233
|View full text |Cite
|
Sign up to set email alerts
|

Making Decisions about Self-Disclosure in Online Social Networks

Abstract: This paper explores privacy calculus decision making processes for online social networks (OSN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…According to Pew Research Center research ( Rainie et al, 2013 ), 28% of Facebook users said the site has become less important to them. Other scholars showed a similar finding that one of the major risks of using social media is it wastes people’s time ( Heravi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 67%
“…According to Pew Research Center research ( Rainie et al, 2013 ), 28% of Facebook users said the site has become less important to them. Other scholars showed a similar finding that one of the major risks of using social media is it wastes people’s time ( Heravi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 67%
“…According to Fig. 10, the social hot-spot of pedestrians is around (15,13) while the hot-spots of Pokémon GO players 390 are located in grid (13,15) and (15,8), where have most of pokémons gathered.…”
Section: Change On Social Network and Social Behaviourmentioning
confidence: 99%
“…were also studied. For example, Heravi et al studied the privacy calculus decision making processes in OSN[15], and David et al found that a static network is more helpful in constructing stronger cooperation than traditional population distribution[16]. Apart from the single social network, there are also few studies about the symbiotic social network.…”
mentioning
confidence: 99%
“…The number of live streaming platforms and the audiences are both remarkably increasing [1,2] recently. For example, Douyu, the biggest live streaming platform in China, announced that the number of active users per month reached to 1.5 billion.…”
Section: Introductionmentioning
confidence: 99%